A spectroscopic and electrochemical investigation of a tetrathiafulvalene series of metal–organic frameworks. (1st November 2018) - Leong, Chanel F.; Wang, Chun-Hai; Ling, Chris D.; D'Alessandro, Deanna M.
Graphical abstract: A tetrathiafulvalene series of metal–organic frameworks, [M2 (TTFTB)(H2 O)2 ] (M = Zn, Mn, Co, Cd; TTFTB = tetrathiafulvalene tetrabenzoate), exhibit radical–radical interactions and intervalence charge transfer between mixed-valence pairs of ligands within the framework structures. Abstract: The series of tetrathiafulvalene (TTF)-based metal–organic frameworks (MOFs) [M2 (TTFTB)(H2 O)2 ] (M = Zn, Mn, Co, Cd; TTFTB = tetrathiafulvalene tetrabenzoate), previously reported to have radical character, have been characterised by electrochemical and spectroscopic techniques to elucidate their electronic properties. The intimate columnar arrangement of the TTF ligands coupled with their low oxidation potential gives rise to radical–radical interactions and intervalence charge transfer between mixed-valence pairs of ligands within the framework structures. These interactions are further promoted in [Zn2 (TTFTB)(H2 O)2 ] (Zn ) by chemical oxidation with I2 which lowers the optical band gap from 2.03 eV to 1.23 eV and increases the conductivity from 2.5(2) × 10 −10 S/cm inZn to 1.6(2) × 10 −9 S/cm in its iodine-doped derivative (I2 @Zn ). This study highlights the importance of combined electrochemical and spectroscopic interrogations of electroactive MOFs towards understanding the origins of their optical and electronic properties.